(untitled) (Research, Society and Development, 2021)
Introduction: Autism Spectrum Disorder, also known as autism, is characterized as a communicative disability, with repetitive behaviors and restricted areas of interest. For this, the identification of the profile of children with the syndrome is of paramount importance, which can provide data to effect public policies. Objective: This study aims to identify the profile of children with Autism Spectrum Disorder. Method: This is a descriptive and exploratory research with a quantitative approach, carried out in an Association of Friends of the Autistic, in the city of Teresina, Piauí, Brazil. The study included medical records of children in the age group from zero to eleven years old attended in 2019. Results: The male gender (80.95%), aged between 8 to 9 years (44.4%) prevailed, Elementary school (1st to 4th grade) (52.4%). 61 (96.82%) had a classification for infantile autism and used drug treatment with Risperidone (23 / 36.5%). The majority (61 / 96.8%) underwent individual therapy and had problems associated with the use of toys, psychomotricity, language, socialization and limits. Conclusion: The study contributes so that professionals are able to perceive the demands of autistic people and collaborate with their best care.